Realizing Food Self-Sufficiency Based on Syirkah bi al-Muzāra’ah Contract in Nusantara Capital City; A Proposal - Susanti, Dyah Ochtorina; Aan Efendi; Suwardi; Auliya Safira Putri (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2025)
This research focuses on the situation of food needs in the new National Capital due to the increasing number of population movements. Its purpose is to analyze the role of the government in realizing proposed food self-sufficiency based on syirkah bi al-muzāra’ah scheme in the Nusantara Capital City area. It used an empirical juridical method that examines the correlation between the principles of sharia economic law and the place or environment studied, namely the Nusantara Capital City. The results of this study show that the role of the government in realizing proposed food self-sufficiency based on the syirkah bi al-muzāra’ah contract in the Nusantara Capital City is evident from 3 (three) elements in the theory of the legal system, namely: First, the legal structure in which the government plays a role as a provider of capital (ṣāḥib al-māl) and infrastructure in realizing food self-sufficiency. Second, the legal substance requires the role of the government in forming strong regulations to achieve food sufficiency in the Nusantara Capital City area. Third, the legal culture so that the concept of syirkah bi al-muzāra’ah can be carried out by complying with local customary norms that are harmonized with sharia principles.